AN ERROR ANALYSIS OF STUDENTS’ DIGITAL WRITING IN USING SENTENCE CONNECTORS AT THE FOURTH SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT OF UIN SUSKA RIAU - Fajar Mubarak; Rizki Amelia (Indonesian Journal of Integrated English Language Teaching, 2022)
The purpose of this research is to explain the dominant error in using sentence connectors in digital writing by the fourth semester students of English Education Department of UIN SUSKA RIAU. This research was a research with descriptive quantitative design. This research was conducted on November 08th, 2021 until February 08th, 2022 at UIN SUSKA RIAU. The subject of this research was the fourth semester students of English Education Department of UIN SUSKA RIAU while the object of this research was students’ error in using sentence connectors in digital writing. The research population of this research consisted of 125 students while the sample of this research was 19 students of the fourth semester of English Education Department of UIN SUSKA RIAU. The researcher employed purposive sampling. The data were collected through documentation. In collecting the data, the researcher used a written documentation from the students’ writing assignment given by the lecturer. The researcher collected and evaluated the result of the students’ assignment by using raters, and the researcher used 2 raters. After collecting the data from raters, the researcher analyzed the data by taking Step of Error Analysis. The result of this study showed that the types of errors found in this research was error of omission which had 36 errors or 46% of total error. Then, error of addition which had 15 errors or 19% of total error. Furthermore, error of misinformation which had 22 errors or 28% of total error. Last, error of misordering which had 5 errors or 7% of total error. In conclusion, the dominant error of students’ digital writing in using sentence connectors at the fourth semester students of English Education Department of UIN SUSKA RIAU was error of omission.